Immunosensor based on immobilization of antigenic peptide NS5A-1 from HCV and silk fibroin in nanostructured films - Moraes, Marli L. [UNESP]; Lima, Lais R. [UNESP]; Silva, Robson R. [UNESP]; Cavicchioli, Mauricio [UNESP]; Ribeiro, Sidney J.L. [UNESP] (My University, 2013)
The peptide NS5A-1 (PPLLESWKDPDYVPPWHG), derived from hepatitis C virus (HCV) NS5A protein, was immobilized into layer-by-layer (LbL) silk fibroin (SF) films. Deposition was monitored by UV-vis absorption measurements at each bilayer deposited. The interaction SF/peptide film induced secondary structure in NS5A-1 as indicated by fluorescence and circular dichroism (CD) measurements. Voltammetric sensor (SF/NS5A-1) properties were observed when the composite film was tested in the presence of anti-HCV. The peptide-silk fibroin interaction studied here showed new architectures for immunosensors based on antigenic peptides and SF as a suitable immobilization matrix. © 2013 American Chemical Society.
Keywords: Antigenic peptides; Hepatitis C virus; Immobilization matrices; Layer-by-layers; Nanostructured Films; Secondary structures; UV-vis absorptions; Voltammetric sensor; Antigens; Composite films; Immunosensors; Viruses; Peptides; antigen; fibroin; immobilized protein; nanomaterial; NS 5 protein, hepatitis C virus; NS-5 protein, hepatitis C virus; peptide fragment; virus protein; amino acid sequence; animal; chemistry; genetic procedures; immunology; methodology; molecular genetics; Amino Acid Sequence; Animals; Biosensing Techniques; Fibroins; Immobilized Proteins; Molecular Sequence Data; Nanostructures; Peptide Fragments; Viral Nonstructural Proteins